PENGARUH PROFITABILITAS, SOLVABILITAS, REPUTASI KAP DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia periode 2012-2014) - Purwa Jati Putri NB (AKT 16 UMY 330, 2016)
This study aimed to analyze the Influence of Profitability, Solvency, Reputation Firm and Firm Size on Audit Delay. Subjects in this study are all manufacturing companies listed in Indonesia Stock Exchange. In this study sample of 153 financial statements that met the study criteria were selected using purposive sampling method. The analysis tool used is multiple linear regression. Based on the analysis that has been done shows that the profitability significantly influence audit delay whereas, Solvency and reputation KAP has no effect on audit delay, company size significantly and negatively related to the audit delay. Keywords: Audit Delay, Profitability, Solvency, Reputation KAP and Company Size.